(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2007)
The use of periodic structures for creation of applicators with the homogeneous or near to him distributing of the electromagnetic field is offered. The given results of modeling of the offered structure and the numerical accounts show prospects of such applicators.